Using a functional approach in solving problems improve performance waterjet equipment - Salenko, O.; Khorolska, М.; Lopata, V.; Solovuch, E.; Kulyzhskyi, V. (Problems of Tribology, 2022)
The paper shows the influence of parameters of the calibration tube jet-abrasive devices on the quality of the process of waterjet cutting critical parts. The results of modeling the formation of two-phase flow and its movement in the calibration tube. Determined that the effects wear ductal fluid of the tube varying intensity and character. In this regard there is the need for functional-oriented approach to the choice of means to ensure the desired geometric parameters of the tube. It is concluded that the decrease in the intensity of ductal Shot material of the tube and thus maintain its geometric parameters is possible by the use of suitable protective coatings , thickness and physical and mechanical characteristics are selected on the basis of Value attributes according to the intensity and type of abrasive loading surface